Economic discourse and the European integration of financial infrastructures and financial markets - Troels Krarup (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2016)
European integration of financial markets appears to repeatedly encounter specific kinds of problems about the substance and limits of the notion of "the market" undergoing integration, and about the status and role of money, market infrastructures, and government within it. Moreover, these problems and the controversies around them parallel classical discussions in economic theory such as that between conceptions of the market as a frictionless space and as a process of competition. A "competitive conception of the market" is identified as producing these parallel problems and controversies in European market integration and economic theory because it implies a contradictory "integration of fragmentation". These themes and parallels can be specifically identified in a recent major project to integrate financial market infrastructures: a pan-European settlement platform - "Target2-Securities (T2S)" - to overcome existing fragmentation between the systems that perform the actual delivery of money and securities from financial transactions. Moreover, a close analysis of T2S answers a question that existing sociological and political economy approaches to European integration - focusing primarily on the interests and ideas of powerful players - struggle with: why T2S will become de facto a monopoly for the European Central Bank when early on in the integration process EU institutions emphasized an industry-led integration. Foucault's notion of "discursive formation" is employed to conceptualize these arguments.
Keywords: 330; European integration; financial infrastructures; financial markets; money; discourse analysis; Target2-Securities; European Central Bank